Gene Silencing Through CRISPR Interference in Bacteria: Current Advances and Future Prospects - Zhang, Riyu; Xu, Wensheng; Shao, Shuai; Wang, Qiyao (Frontiers in Microbiology, 2021)
Functional genetic screening as an important method has been widely used to explore biological processes and functional annotation of genetic elements. CRISPR/Cas (Clustered regularly interspaced short palindromic repeat sequences/CRISPR-associated protein) is the newest tool in the geneticist's toolbox, allowing researchers to edit genome with unprecedented ease, accuracy, and high-throughput. Most recently, CRISPR interference (CRISPRi) has been developed as an emerging technology that exploits the catalytically inactive Cas9 (dCas9) and single-guide RNA (sgRNA) to repress sequence-specific genes. In this review, we summarized the characterization of the CRISPRi system, such as programmable, high efficient, and specific. Moreover, we demonstrated its applications in functional genetic screening and highlighted its potential to dissect the underlying mechanism of pathogenesis. The recent development of CRISPRi system will provide a high-throughput, practical and efficient tool for the discovery of functionally important genes in bacteria.